2018
DOI: 10.1111/imr.12686
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dynamics of hepatitis B infection, immunity, and drug therapy

Abstract: Hepatitis B virus infection is the cause of liver diseases such as cirrhosis and liver cancer. Understanding the host-virus mechanisms that mediate virus pathogenesis can help design better preventive measures for disease control. Mathematical models have been used alongside experimental data to provide insight into the role of immune responses during the acute and chronic hepatitis B infections as well as virus dynamics following administration of combined drug therapy. In this paper, we review several modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 118 publications
(318 reference statements)
0
25
0
Order By: Relevance
“…Overall, HbxAg is the key factor and plays a central role in the development of HCC. HBV genome encodes four overlapping open reading frames (ORF), of which X ORF is one [14]. X ORF encodes a 16.5 kDa protein, HbxAg, which has multiple functions.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, HbxAg is the key factor and plays a central role in the development of HCC. HBV genome encodes four overlapping open reading frames (ORF), of which X ORF is one [14]. X ORF encodes a 16.5 kDa protein, HbxAg, which has multiple functions.…”
Section: Discussionmentioning
confidence: 99%
“…Applications have been summarized in a recent issue of Immunological Reviews (3), showing their relevance for understanding the host-pathogen interactions in both chronic and acute infections (4)(5)(6). In the last decade, parameter estimation of these models has increasingly relied on nonlinear mixed effect models (NLMEM), a statistical approach that improves both precision and accuracy of estimates by explicitly taking into account the between-subjects variability in the model (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we developed mathematical models that best reproduce observed HBV DNA, HBsAg and HBeAg kinetics following a single dose of ARC-520 in five HBeAg-positive patients from the Heparc-2001 study. Mathematical models of hepatitis B infection have been used to study the dynamics of acute, chronic, and occult HBV infections [20][21][22][23][24], anti-HBV therapy [14,[25][26][27][28][29][30], cell-to-cell transmission [31] , intracellular interactions [31][32][33], cellular immune responses [21,25,[34][35][36], antibody-mediated immune responses [11,33,37], HBeAg [33,38,39], and HBeAb [33] dynamics. We build on previous modeling work, consider the interaction between HBV DNA, HBsAg and HBeAg titers in the presence of a single dose RNAi-based therapy, and use the model to run in silico experiments to predict individual contributions of different drug effects on 2/23 the dynamics for HBsAg titers.…”
Section: Introductionmentioning
confidence: 99%